2018
DOI: 10.1016/j.celrep.2018.06.039
|View full text |Cite
|
Sign up to set email alerts
|

A Hepatocyte FOXN3-α Cell Glucagon Axis Regulates Fasting Glucose

Abstract: SUMMARY The common genetic variation at rs8004664 in the FOXN3 gene is independently and significantly associated with fasting blood glucose, but not insulin, in non-diabetic humans. Recently, we reported that primary hepatocytes from rs8004664 hyperglycemia risk allele carriers have increased FOXN3 transcript and protein levels and liver-limited overexpression of human FOXN3, a transcriptional repressor that had not been implicated in metabolic regulation previously, increases fasting blood glucose in zebrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…1C and D). These results mirror the effects seen in zebrafish mutants carrying a heterozygous foxn3 loss-of-function allele where a 50% reduction in foxn3 transcript was accompanied by a twofold increase in mycb transcript (Karanth et al, 2018). These effects are also similar to that observed when immortalized human cells are transduced with a dominant-negative FOXN3 cDNA that occurs in leukemia as a consequence of pathological intron polyadenylation (Lee et al, 2018).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…1C and D). These results mirror the effects seen in zebrafish mutants carrying a heterozygous foxn3 loss-of-function allele where a 50% reduction in foxn3 transcript was accompanied by a twofold increase in mycb transcript (Karanth et al, 2018). These effects are also similar to that observed when immortalized human cells are transduced with a dominant-negative FOXN3 cDNA that occurs in leukemia as a consequence of pathological intron polyadenylation (Lee et al, 2018).…”
Section: Resultssupporting
confidence: 74%
“…We modeled this increase in liver FOXN3 by transgenic over-expression of human FOXN3 in zebrafish hepatocytes, and observed an increase in fasting blood glucose in animals fed their normal diets (Karanth et al, 2016). Conversely, deletion of the foxn3 ortholog in zebrafish decreases fasting glucose (Karanth et al, 2018). On a mechanistic level, FOXN3 regulates fasting blood glucose by directly repressing expression of MYC (Karanth et al, 2016), a transcription factor central to promoting glucose utilization in liver (Sloan and Ayer, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcription factor forkhead box N3 (FOXN3), as a member of the forkhead box N superfamily, participates in several biological processes, including the cell cycle, cell differentiation, epithelial‐mesenchymal transition, gene transcription and glucose metabolism . Previous studies have shown that the downregulated expression of FOXN3 is observed in various malignancies, such as hepatocellular carcinoma (HCC), colon cancer, ERα‐positive breast cancer, Hodgkin lymphoma, head and neck cancer, lung cancer, adult glioblastoma multiforme, T cell acute lymphoblastic leukaemia (ALL) and osteosarcoma, and the FOXN3 expression level is associated with the prognosis of some cancers …”
Section: Introductionmentioning
confidence: 99%